Concern for the Sobriety of Youth in Młody Hufiec in 1927-1939 - Biskupski, Jacek (Biuletyn Historii Wychowania, 2018)
Alcohol abuse among young people was a serious social problem in the interwar period. The aim of the article is to show how the Młody Hufiec magazine attempted to oppose the commonly accepted drunkenness of youth in Poland. The article describes actions undertaken in order to combat alcoholism and promote abstinence among youth, published by the magazine in 1927–1939.